ATENCIÓN SOSTENIDA EN LA LECTURA COMPRENSIVA EN LOS ESTUDIANTES DE LA UNIDAD EDUCATIVA “NUESTRO MUNDO ECO-RIO”, PERÍODO ABRIL- AGOSTO 2019. - Andrade Véliz, Gina Lilibeth (2020)
The main objective of this research was to determine the level of sustained attention and comprehensive reading by analyzing the correspondence relationship in the students of 4th year of Basic General Education, of the Educational Unit "Our World ECO RIO", period April-August 2019, for which it must be taken into consideration that the sustained attention is of the utmost importance in the development of the teaching-learning process and in a concrete way in the comprehensive reading, thus allowing the students to generate reasoning, analysis and autonomy processes. The sample was of an intentional non-probabilistic type settling in 43 students, methodologically working with the design of non-experimental research, the type of research is field, cross-sectional by the level of research is descriptive and correlational. The technique that was used for the variable of sustained attention was the Brickenkamp D2 test of the year 1962 and modified by N. Seisdedos and for the comprehensive reading variable an observation sheet, we also worked with the SPSS-21 program for the analysis of data. As a result of the investigation, a positive and direct correlation was determined, regarding the variables given that the effectiveness was evidenced in the percentages from medium to high level.